CONGENITAL SCAPHOID MEGALOURETHRA: REVISITING A RARE ANOMALY - Zahoor, Ilyas; Asif, Mohammad; Khan, Sarhad; Haroon, Naveed (Journal of Ayub Medical College Abbottabad, 2022)
Megalourethra is an infrequent malformation of the anterior urethra that is caused by the lack of corpus sponigosum and in severe cases is accompanied by the lack of corpora cavernosa as well. We report a five-year-old boy presented to us with scaphoid variety of megalourethra having complaints of ballooning of urethra during voiding. He was investigated with urethrogram and cystoscopy and subsequently repaired with Nesbitt Longitudinal Reduction Urethroplasty. He had smooth recovery postoperatively with normal voiding stream on follow up.